math

posted by .

how do you solve the exponential equation, 12^x = 14^3x?
If someone could show me step by step I would greatly appreciate it.
thank you! :)

  • math -

    (12)^x = (14)^3x.

    X*log12 = 3X*log14,
    X * 1.08 = 3X * 1.15,
    1.08X = 3.45X,
    1.08X - 3.45X = 0,
    -2.37X = 0,
    X = 0 / -2.37 = 0.

    CHECK:

    (12)^0 = (14)^0,
    Any number raised to the zero power=1:
    1 = 1.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Pre-Algebra [urgent!]

    I can't find the solution to this problem; can someone please show me how to solve it step-by-step?
  2. TRIGONOMETRY

    Can someone please show me step by step solutions?
  3. math

    Can someone please show me step by step how to solve this, I've been stuck. Find the common ration r of the geometric series an that satisfies the following conditions: c=4, S=16 I would reallyy appreciate it if someone could help …
  4. algebra

    Im lost i don't know how to do this can someone show me step by step how to solve this For what value does c does the equation have one real root?
  5. algebra

    Im lost i don't know how to do this can someone show me step by step how to solve this For what value of c does the equation have one real root?
  6. Algebra 1--Step-by-Step

    Can someone show me how to solve these step-by-step?
  7. algebra

    solve each exponential equation. Given the value for x 8^x=1/64 3^x=6 Can someone show me how to preform these. I would greatly appreciate it Thank You
  8. Calculus

    Hello, I really need help on these two homework problem. >< In problem #1, I believe it is related to the exponential functions and their derivatives section...in Calculus II?
  9. math

    I know you have to group this problem but I'm not sure how to solve this, if someone could step by step I would appreciate it. 6x^3 +14x^2-27x-63
  10. Math

    I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 − …

More Similar Questions